Features of diagnosis and treatment of gastrointestinal stromal tumors - N. I. Bogomolov; T. V. Burdinskaya; M. A. Goncharova; A. G. Goncharov; N. N. Tomskikh (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To analyze the data of patients with gastrointestinal stromal tumors (GIST) in the retrospective study that was carried out in hospitals of Chita and central regional hospital of Transbaykal region. Material and methods. In original study overall 116 patients with stromal tumors of gastrointestinal tract according to the records of Chita and Transbaikal Regional pathological bureau were analyzed Results. Nine (7,7%) patients had tumor location in the esophagus, 69 (59,4%) - in the stomach, 3 (2,5%) - in duodenum, 16 (13,7%) - in jejunum and ileum, 10 (8,6%) - in the colon, 3 (2,5%) - in the rectum. Retroperitoneal location of the GIST was revealed in 3 (2,5%) patients, pancreatic - in 2 (1,7%), liver - in 1 (0,8%) patient. The tumor was complicated by development of gastro-intestinal bleeding in 51 (44,8%) patients, in 3 cases (2,5%) it was lethal. Patients underwent organ-preserving operations without lymphadenectomy. In the remote period after surgery one patient died due to tumor metastasis, in 7 patients GIST was primarily diagnosed at the autopsy. Targeted therapy by tyrosine kinase inhibitors was carried out for 14 patients. Histological investigation of tumors revealed the mixed type in 8,62% of patients, and approximately equal proportion for spindle-cell and epithelioid (46,4 and 44,8%) variants. Extraorgan tumor growth especially in the cases of gastric location, commonly led to diagnostic errors when GIST was misdiagnosed for pancreatic pseudocyst, leiomyoma, schwannoma and other tumors. Conclusions. GIST can develop in any segment of gastrointestinal tract and features extraorgan growth in most of the patients, intraluminal growth of pedunculated tumor is rarely diagnosed. Bleeding from a tumor is the most frequent complication which can which can be lethal.